2007
DOI: 10.1203/pdr.0b013e3180459f8a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Serum Adiponectin Concentration on Birth Size and Early Postnatal Growth

Abstract: ABSTRACT:In term neonates, the adiponectin concentration is higher than it is in adults. To determine the relationship between adiponectin and early neonatal growth in a cohort study. Fifty-two neonates at term were studied. Serum adiponectin concentrations, body sizes, and skinfold thicknesses were measured at birth and at 1 mo of age. At birth, cord blood adiponectin concentration correlated positively with birth weight (r ϭ 0.484, p ϭ 0.0003), birth length (r ϭ 0.524, p Ͻ 0.0001), and sum of the four skinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 26 publications
3
56
0
Order By: Relevance
“…In our previous cohort study of term infants (69), cord blood adiponectin levels were strongly related to birth weight and skinfold thickness; however, these relationships were not demonstrated in 1-mo-old infants. Adiponectin levels increased markedly during 1 mo along with s.c. fat accumulation.…”
Section: Adiponectinmentioning
confidence: 61%
“…In our previous cohort study of term infants (69), cord blood adiponectin levels were strongly related to birth weight and skinfold thickness; however, these relationships were not demonstrated in 1-mo-old infants. Adiponectin levels increased markedly during 1 mo along with s.c. fat accumulation.…”
Section: Adiponectinmentioning
confidence: 61%
“…Inami et al [26] have demonstrated that neither the mean change in body weight/body length, nor skinfold thickness correlates with the changes in adiponectin levels from birth to 1 month of age in term neonates despite a positive relationship between cord adiponectin levels and birth length, suggesting that adiponectin has an effect on fetal growth, but no effect on early postnatal growth. Similarly, an investigation in a large number of term newborns showed that growth velocity during the first week of life was positively associated with serum insulin-like growth factor-I levels, but not serum adiponectin levels [27,28] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, cord blood leptin levels, and not HMW-ad, were significantly associated with birth weight to length ratio in the multiple regression analysis. The birth weight to length ratio seems to be associated with body fat content [25]. Thus, cord blood leptin concentrations may have a stronger association with fat content in neonates as compared with those of adiponectin concentrations.…”
Section: Discussionmentioning
confidence: 99%